Gambaran Status Periodontitis Paska Perawatan Scaling Dan Root Planing Pada Wanita Menopause(Kajian Pada Posyandu Lansia Mawar XII Kelurahan Pajang Kecamatan Laweyan) - Putri, Yutika Difa Nendya, drg. Edi Karyadi, M.M (2016)
Background: Decreased estrogen in postmenopausal women caused problems in the oral cavity, one of which is periodontitis. Prevalence of periodontitis in age >75 years (18,32%) is greater than the age of 65-74 years (13,11%). The first conducted of Periodontal treatment is scaling and root planing. Purpose: the aim of this research was to review the status changed periodontitis treatment after scaling and root planing on 10 postmenopausal women with periodontitis in Posyandu Mawar District of Laweyan. Methods: The sampling technique in this study using purposive sampling. Clinical examination performed before and 2 weeks after treatment. The indicators used are Periodontal Pocket Depth (PPD), and Clinical Attachment Loss (CAL). And then the status of periodontitis is classified according to the Centers for Disease Control and Prevention (CDC) in collaboration with the American Academy of Periodontology (AAP) based on the measurement of pocket depth (PD) and clinical attachment loss (CAL). Results: There are a decrease in average across all clinical parameters. PPD scores decreased from 3.4 to 2.7, and the score CAL decreased from 4.2 into 3.4. and obtained status periodontitis before treatment in the category mild 1 person, moderate 4 persons, and severe 5 persons. And changes were satisfy after treatment to 5 persons in mild category, and 5 persons in moderate category. (p=0,000) Conclusion: Overall, the results showed that the treatment effectively scaling and root planing for periodontitis lowered the status of because it can reduce the number of pathogenic bacteria and periodontal repair damaged tissue.